Consumer Attitudes And Adoption Of Internet Banking In Malaysia - Lin, Chan Yee (2004)
This study investigates attitudes between adopters and non-adopters on Internet banking adoption. Besides, it also examines the importance of factors that hinder Internet banking adoption.